Effect of TNF inhibitors on lipid profile in rheumatoid arthritis: a systematic review with meta-analysis. Issue 6 (20th January 2012) - Daïen, Claire Immediato; Duny, Yohan; Barnetche, Thomas; Daurès, Jean-Pierre; Combe, Bernard; Morel, Jacques
Abstract : Background: Patients with rheumatoid arthritis (RA) are at increased risk of cardiovascular disease. Lipid changes related to inflammation have been described in RA. Tumour necrosis factor α (TNFα) inhibitor (TNFi) treatment is effective in controlling inflammation and decreasing the number of cardiovascular events. Objective: To assess the change in lipid levels with TNFi treatment in patients with RA by systematic review and meta-analysis. Methods: A Medline search was performed for articles published up to March 2011. Reports describing values for total cholesterol (TC), low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides (TGs), atherogenic index (AI) and apolipoprotein B/A (apoB/A) collected before and after TNFi initiation were included. Data were analysed according to short-, mid- and long-term treatment. Statistical analysis of pre–post data was performed by comprehensive meta-analysis. A random effects model was used when there was evidence of heterogeneity. Results: The search retrieved 32 articles, of which 13 prospective before/after studies were analysed. Long-term TNFi treatment was associated with increased levels of HDL (+0.27 mmol/l, p<0.0001) and TC (+0.27 mmol/l, p=0.03), whereas LDL levels and AI remained unchanged. After long-term treatment, TG levels increased (+0.28 mmol/l, p<0.001) and apoB/A decreased (−0.3, p<0.0001). Conclusion: The presumed cardioprotective effects of TNFi in RA do not seem to be explained by quantitative lipid changes since long-term treatment has no effect on LDL levels or on AI. Increased HDL levels could have some beneficial effects, but this needs to be confirmed by prospective studies with long-term follow-up.